PREVALENCE OF DYSLIPIDEMIA: A STUDY OF LIPID PROFILE FINDINGS AT A PRIVATE CLINICAL LABORATORY IN TANGERANG CITY - Enny Irawaty; Novendy Novendy (Ebers Papyrus, 2026)
Dyslipidemia is a metabolic disorder of blood lipids and a global public health issue that affects millions of people, increasing the risk of cardiovascular diseases and the leading cause of death worldwide. The prevalence of dyslipidemia among adults is estimated between 20% - 80%. Several factors contribute to the growing burden of dyslipidemia, one of which is the low rate of accurate diagnosis. This is further exacerbated by the insufficient testing and monitoring of LDL cholesterol levels in the general population, which hinders early detection and effective intervention. A clinical laboratory located in the city of Tangerang frequently provides blood lipid profile testing for patients. However, the results of these tests have not yet been analysed to assess the extent of dyslipidemia related issues. Therefore, a study was conducted to evaluate the distribution of blood lipid profile results and determine the prevalence of dyslipidemia in the population. Cross sectional design was used in this study. A total of 470 data were collected. The study found that the prevalence of dyslipidemia was 26.2%. In addition, 15.7% of individuals had high total cholesterol levels, 8.9% had elevated triglycerides, 8.5% had low HDL levels, and 15.3% had high LDL levels. Routine monitoring of blood lipid levels is crucial for the early detection of lipid metabolism disorders such as dyslipidemia. With regular monitoring, changes in lipid levels can be identified and addressed promptly. Therefore, blood lipid monitoring is an essential preventive measure in maintaining cardiovascular health and improving a quality of life.